Dokumentasi Budaya Pengangkatan Pangulu Di Tanah Tasirah Di Kanagarian Lareh Nan Panjang Kota Padang Panjang - Khairanis, Ulva; Rohanda, Rohanda; Yanto, Andri (Ilmu Informasi Perpustakaan dan Kearsipan, 2022)
Pangulu inauguration ceremony is an activity for appointment of traditional leaders that occurs in West Sumatera region. The strong oral tradition in Minangkabau region causes the lack of written works and documentation that has an impact oncultural preservation. This study aims to document the process of holding the pangulu in tanah tasirah in Kanagariah Lareh Nan Panjang, Padang Panjang City. The research method used is a qualitative method with an action research approach. This research also uses the documentation process model. Sources of data were obtained from interviews and document studies related to the pangulu inauguration ceremony. The result of the research is a product of cultural documentatuon in the form of a reference book. This cultural documentation book is available in two froms: printed and electronic (e-book). The results of the public test show that this cultural documentation book is easy for readers to understand.